Validated Designs for Object-oriented Systems - Fitzgerald, John; Larsen, Peter Gorm; Mukherjee, Paul; Plat, Nico; Verhoef, Marcel (Springer London : Imprint: Springer, 2005)
Object-oriented design methods are commonplace in computing systems development, but are often dismissed as 'boxes & arrows'. If systems developers are to gain full advantage from such methods, they should be able to achieve designs that are not merely the subject of heated argument, but can be improved by careful, rigorous & machine-supported analysis. This book describes an object-oriented design approach that combines the benefits of abstract modelling with the analytic power of formal methods, to give designs that can be rigorously validated & assured with automated support. Aimed at software architects, designers & developers as well as computer scientists, no prior knowledge of formal methods is assumed. The elements of functional modelling are introduced using numerous examples & exercises, industrial case studies & experience reports. Industry-strength tools support the text. Go to www.vdmbook.com to download free-of-charge VDMTools Lite, which gives the possibility to try out examples from the book.